Character Education Values in the Lyrics Of “Cangkurileung” Songs by Mang Koko - Sofyan, I Wahyudi; Sudaryat, Yayat; Kuswari, Usep (CV. Goresan Pena, 2024)
Mang Koko is a second-generation artist after Raden Machyar Anggakoesoemadinata, who was involved in the history of Sundanese traditional music (karawitan) development in the 20th century. He created hundreds of traditional Sundanese songs that remain popular and cherished by the Sundanese community today. Due to his creativity and the diversity of his works, he is recognized as a reformer in Sundanese traditional music. Besides being skilled in arranging songs, Mang Koko was adept at composing lyrics. One of his works is compiled in the Cangkurileung Volumes 1–3 songbook series. This paper aims to explore and reveal the values of character education embedded in the lyrics of these songs. The method used is descriptive, employing literature review techniques. The results indicate that the lyrics of Cangkurileung contain character education values that serve as guidelines for both the present and the future.